Importance of orchard floor management in organic fruit growing (nutritional aspects) - Nagy, P. T.; Kincses, I.; Lang, T.; Szőke, S. L.; Nyéki, J.; Szabó, Z. (International Journal of Horticultural Science, 2010)
Worldwide research goals and concerns are to soil conservation and improve. This conception is mostly actual in horticulture where the numbers of high-density plantings are continuously increasing. High-density orchards cause more intensive nutrient and water uptake. So that the preservation of soil moisture and nutrient level are key factors in qualified fruit growing. On the other hand due to the climatic changes the water supply of trees will be satisfied among worse conditions than some decades ago. Appearance of water supply problems and water stress is increased in organic growing, where the number of corrections is limited anyway. Furthermore, floor management is a successful tool in weed management which causes many problems for organic growers due to the prohibition of synthetic herbicides. This paper will mainly focus on the nutritional aspects of methods of orchard floor management for growers adopting organic fruit management to make their production profitable.